Analysis of modern possibility of increasing the quality of training for electric power industry Ukraine - Полковніченко, Дмитро Вікторович; Москвіна, Ірина Ігорівна (Technology audit and production reserves, 2015)
This paper analyzes the main problems existing in professional education Ukraine, which resulted in a low level of training that does not meet the needs of employers in the electricity sector. The analysis showed that the main problems are: the isolation of the educational system of real production; imperfect system of formation of state order for training; old practice of financing and management of education; level of logistics universities; high academic load of teachers; decline in the prestige of engineering specialties. Past research excellence of modern methods of education have shown that to solve the existing problems, the following measures: the development and introduction of professional standards that help to hold the relationship between the demands of employers and university curricula; establishing close cooperation between educational institutions and manufacturing enterprises, namely improving career guidance, strengthen employers on stage as a professional choice and student learning, and to ensure his employment; comply with the current level of production of material and technical base of vocational education; reduce workload for teachers that will thoroughly prepare for lectures and continually improve their level in line with modern trends of science and technology; improving the monitoring of and evaluation system by implementing and testing simulators specially adapted.